2013
DOI: 10.1016/j.jadohealth.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Partner Accumulation From Adolescence Through Early Adulthood: The Role of Family, Peer, and School Social Norms

Abstract: Purpose An early age of sexual initiation and sexual activity with multiple partners are risk factors for an array of detrimental outcomes. Drawing on social norms theory, this study assessed the role of subjective and descriptive social norms from parents, peers, and schoolmates on trajectories of sexual partner accumulation from early adolescence through early adulthood. Methods Data were drawn from the in-home survey sample of Add Health, following 14,797 youth from adolescence through early adulthood. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 17 publications
0
42
2
1
Order By: Relevance
“…My findings align with previous research, whereby college students reported having more frequent and comprehensive conversations with their friends about sex and romantic relationships than they do with their parents (Lefkowitz & Espinosa-Hernandez, 2007; Levin, Ward, & Neilson, 2012). The difference between the current study’s more conservative characterization of friends’ sexual communications and previous research’s (e.g., Coley, Lombardi, Lynch, Mahalik, & Sims, 2013; Kenney, Thadani, Ghaidarov, & LaBrie, 2013) characterization of more permissive peer sexual norms may be due to pluralistic ignorance. That is, young people may consistently overestimate the extent to which they believe their peers have permissive sexual attitudes and take sexual risks (Chock, 2011; Holman & Sillars, 2012; Lewis, Lee, Patrick, & Fossos, 2007).…”
Section: Discussioncontrasting
confidence: 92%
“…My findings align with previous research, whereby college students reported having more frequent and comprehensive conversations with their friends about sex and romantic relationships than they do with their parents (Lefkowitz & Espinosa-Hernandez, 2007; Levin, Ward, & Neilson, 2012). The difference between the current study’s more conservative characterization of friends’ sexual communications and previous research’s (e.g., Coley, Lombardi, Lynch, Mahalik, & Sims, 2013; Kenney, Thadani, Ghaidarov, & LaBrie, 2013) characterization of more permissive peer sexual norms may be due to pluralistic ignorance. That is, young people may consistently overestimate the extent to which they believe their peers have permissive sexual attitudes and take sexual risks (Chock, 2011; Holman & Sillars, 2012; Lewis, Lee, Patrick, & Fossos, 2007).…”
Section: Discussioncontrasting
confidence: 92%
“…The spatial parameters for casual sex and unprotected sex are both significant at the 5 % level, while the spatial parameter for multiple partners is insignificant. Recent work has shown that looking at peer influence as occurring through social norms can explain the significant effects (Coley et al 2013; Wisnieski et al 2013). The following tables provide the results of the marginal effects of peer influences.…”
Section: Resultsmentioning
confidence: 99%
“…For example, local neighborhood norms about sex are associated with adolescent sexual behavior: Adolescents in neighborhoods with less restrictive norms are more likely to have sex, casual sex, and more sexual partners (Warner et al, 2011). Similarly, adolescents who attend high schools with fewer virgins are less likely to remain virgins themselves (Regnerus, 2007) and to accumulate more sexual partners (Coley et al, 2013). These findings suggest that individuals take cues from the attitudes and behavior of those around them and factor them into their own sexual decision-making.…”
Section: Institutional Characteristicsmentioning
confidence: 99%